(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
hough the African human rights protection system has enshrined as absolute the right not to be subjected to acts of torture or cruel, inhuman or degrading punishment or treatment, these practices, which disregard the inherent dignity of thehuman person, continue to thrive on the continent. This state of affairs begs the question whether the prohibition and repression of torture are pure utopia or evidence of the bad faith of states. This study aims to answer this question. It sets out, first, the relevant legal instruments in this area, as well as the mandate of the Committee for the Prevention of Torture in Africa, responsible for promoting the implementation of the Robben Island Guidelines. It then provides an overview of the situation by studying the ratifications and complaints submitted to African supranational bodies. It also presents national shortcomings both in the adoption of legislation and in the creation of specific bodies, as well as in complacency at the repression stage. It ends with theproposal of recommendations to improve the effectiveness of the fight against torture.